Clinical Social Work Journal - Saari, Carolyn; Tosone, Carol; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Clinical Social Work Journal is an international forum devoted to the advancement of clinical knowledge and acumen of practitioners, educators, researchers, and policymakers. The journal, founded in 1973, publishes leading peer-reviewed original articles germane to contemporary clinical practice with individuals, couples, families, and groups, and welcomes submissions that reflect innovations in theoretical, practice , evidence-based clinical research, and interdisciplinary approaches.
Keywords: Clinical psychology; Personality; Social psychology; Clinical Psychology; Personality and Social Psychology